Entertainment as a Complex Form of Communication. Two Examples of Hemsöborna. - Strömberg, Mikael (Nordic Theatre Studies, 2016)
An increasing interest in popular culture, entertainment, and leisure studies has resulted in a more thorough discussion of entertainment and its function in everyday life. That entertainment needs to be studied on its own terms, and not just in relation to some other area, is important. Instead of viewing entertainment as merely something connected with enjoyment and pleasure, the article looks at how entertainment renegotiates vital questions and topics from everyday life through its performance practice. Entertainment is used as an enhanced awareness, a de-familiarization, illustrating the function of different norms. The article examines two different scenes from two different productions of August Strindberg’s novel The People of Hemsö. The first analyses the arrival of an outsider, coming from the mainland to the archipelago. The second underlines the seriousness of gender inequality. Both examples stress the importance of studying how entertainment functions as a specific performance style/practice that re-negotiates the content being communicated.